Designing an Interactive Digital Magazine E-Module to Foster Mathematical Problem-Solving Skills through Differentiated Instruction - Nadhiya, Bayva; Syafmen, Wardi; Novferma, Novferma (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
A major challenge in junior high school mathematics learning, particularly in the topic of Systems of Linear Equations in Two Variables (SLETV), lies in students’ low problem-solving ability, stemming from instructional materials that fail to accommodate diverse learning styles. This study aims to develop and evaluate an interactive digital magazine based e-module that integrates Problem Based Learning (PBL) and supports differentiated instruction to enhance students’ mathematical problem-solving skills. A development research design was employed using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Participants included subject-matter experts, media experts, mathematics teachers, and eighth-grade students at SMPN 7 Jambi City. Instruments consisted of validation questionnaires, practicality questionnaires, and problem-solving tests. The research procedure covered expert validation, individual testing, small-group testing, and large-group testing. Quantitative data were analyzed using statistical software to assess validity, practicality, and effectiveness. Results show that the e-module is highly valid, practical, and effective in improving students’ problem-solving ability, as indicated by the N-Gain scores. This interactive e-module offers a promising alternative instructional medium that supports differentiated instruction and contributes to the development of 21st-century skills.